2020
DOI: 10.1108/er-08-2019-0320
|View full text |Cite
|
Sign up to set email alerts
|

How do human resource management practices affect employee well-being? A mediated moderation model

Abstract: PurposeThe study examines how human resource management practices (HRMPs) – including ability practice, motivation practice and opportunity practice – affect employee well-being (EWB) – including life well-being, job well-being and psychological well-being – in the Chinese cultural context.Design/methodology/approachA sample of 529 employees from various industries in China participated in the survey for this study. Data were analyzed using structural equation modeling.FindingsThe findings indicate that HRMPs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 44 publications
2
41
0
9
Order By: Relevance
“…Overall, subjective wellbeing motivates and fuels the accomplishment of goals throughout life's challenges. In the work environment, research suggests that employees with high subjective wellbeing tend to be more creative, productive, and resilient (Zhang et al, 2020). In the context of tourism, resident subjective wellbeing is believed to be an important factor for sustainable tourism development (Chi, Cai, & Li, 2017) and studies have suggested that residents who experience high subjective wellbeing are willing to support tourism development and engage in value co-creation with tourists (Lin et al, 2017).…”
Section: Subjective Wellbeingmentioning
confidence: 99%
“…Overall, subjective wellbeing motivates and fuels the accomplishment of goals throughout life's challenges. In the work environment, research suggests that employees with high subjective wellbeing tend to be more creative, productive, and resilient (Zhang et al, 2020). In the context of tourism, resident subjective wellbeing is believed to be an important factor for sustainable tourism development (Chi, Cai, & Li, 2017) and studies have suggested that residents who experience high subjective wellbeing are willing to support tourism development and engage in value co-creation with tourists (Lin et al, 2017).…”
Section: Subjective Wellbeingmentioning
confidence: 99%
“…A good understanding of which physical, emotional and behavioral symptoms of health problems do employees face during the COVID-19 epidemic could improve better health, well-being, productivity and satisfaction among employees during the COVID-19 and also after the COVID-19. According to Lee (2021), Agus and Selvaraj (2020), Srivastava and Agarwal (2020), Zhang et al (2020), Shareena and Mahammad (2020) and Hayes and Curran (2020), there is more need for suitable human resource management during the COVID-19 epidemic and suitable working environment for employees during the COVID-19 epidemic and also after the COVID-19 epidemic. Moreover, Stein (2020), Gavidia ( 2020 The study findings show that physical, emotional and behavioral symptoms of health problems among employees during the COVID-19 epidemic are more strongly expressed as before the COVID-19 epidemic, and also the study findings show that there are significant differences regarding physical, emotional, and behavioral symptoms of health problems among employees who worked from home and those who worked at the workplace during the COVID-19 epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, employees perform better when they are healthy and happy [3,4]. Therefore, raising employee well-being is a critical topic in organizational development [5]. Research has indicated that social support is connected with work-related well-being [6], such as work engagement [7,8], and it is also connected with subjective well-being in personal life [9,10].…”
Section: Introductionmentioning
confidence: 99%